The Sella Turcica dimensions in 12-year-old Southern Chinese: a cross-sectional study - Mohd Zambri Mohamed Makhbul; Wan Nurazreena Wan Hassan; Wong, Ricky Wing Kit (Penerbit Universiti Kebangsaan Malaysia, 2019)
The objective of the study was to measure the dimensions of the sella turcica in southern Chinese population. This retrospective study measured dimensions of sella turcica from lateral cephalometric radiographs obtained from the University of Hong Kong research database with a total of 582 (277 females and 305 males) 12-year-old southern Chinese children, who were randomly selected from schools in Hong Kong. Measurements were made using ImageJ (V1.45s) software for Windows with Frankfurt plane as the horizontal reference direction. Dimensions between genders were compared using Student’s t-tests. The current study found the antero-posterior length and width were 9.13 mm (SD 2.05) and 9.76 mm (SD 1.54), respectively. The sella was highest posteriorly (7.97 mm; SD 1.75 mm) and shortest anteriorly (7.56 mm; SD 1.42). Sella height anterior, sella height median and sella area were greater (p<0.05) in females by 0.53 mm, 0.24 mm and 3.48 mm2, respectively. In conclusion, this study provides the reference parameters for the dimensions of sella turcica for the Southern Chinese population.